Isotopic fractionation of cadmium into calcite - Horner, T; Rickaby, R; Henderson, G (2011)
Cadmium mimics the distribution of the macronutrient phosphate in the oceans, and has uses as a palaeoproxy of past ocean circulation and nutrient utilization. Isotopic analyses of dissolved Cd in modern seawater show potential as a new tool for disentangling phytoplankton utilization of Cd from abiotic processes, such as ocean mixing. Extending this information into the past requires the Cd isotope signal to be captured and faithfully preserved in a suitable sedimentary archive. However, the role that environmental factors, such as temperature, may play in controlling Cd isotope fractionation into such archives has not been assessed. To this end, we have performed controlled inorganic CaCO3 precipitation experiments in artificial seawater solutions. We grew calcite under different precipitation rates, temperatures, salinities, and ambient [Mg2+], before measuring Cd isotopic compositions by double spike MC-ICPMS. We find that the isotopic (αCaCO3-Cdaq) in seawater is always less than one (i.e. light isotopes of Cd are preferred in calcite). The fractionation factor has a value of 0.99955±0.00012 and shows no response to temperature, [Mg2+], or precipitation rate across the range studied. The constancy of this fractionation in seawater suggests that marine calcites may provide a record of the local seawater composition, without the need to correct for effects due to environmental variables. We also performed CaCO3 growth in freshwater and, in contrast to calcite precipitated from artificial seawater solutions, no isotopic offset was recorded between the growth solution and calcite (αCaCO3-Cdaq=1.0000±0.0001). Cadmium isotope fractionation during calcite growth can be explained by a kinetic isotope effect during the largely unidirectional incorporation of Cd at the mineral surface. Further, the rate of Cd uptake and isotopic fractionation can be modulated by increased ion blocking of crystal surface sites at high salinity. The fractionation of Cd isotopes observed during precipitation of calcite has the same direction and similar magnitude to that implicated for Cd removal from the surface ocean by seawater measurements. However, flux calculations show that CaCO3 precipitation is unlikely to play a significant role in setting the Cd isotope composition in seawater, compared to Cd utilization in phytoplankton soft tissue. Marine carbonates therefore record seawater Cd isotope chemistry - with potential as a palaeoceanographic proxy - rather than drive oceanic Cd isotope compositions. © 2011 Elsevier B.V.